Faktor-faktor yang Mempengaruhi Profitabilitas Bank Syariah di Asia Pasifik Tahun 2010-2016 - Haryadi, Anton (STIES ALIFA, 2022)
The purpose of this study is to examine the impact of several factors, namely Capital Adequacy Ratio (CAR), Bank Size, Technology (Internet Banking), and Gross Domestic Product (GDP) on the profitability or Return On Asset (ROA) of Islamic banks operating in the Asia Pacific region between 2010-2016. The sample consists of six Islamic banks located in this region. Data for the variables